2020
DOI: 10.1039/d0nj02316g
|View full text |Cite
|
Sign up to set email alerts
|

DFT and hybrid-DFT calculations on the electronic properties of vanadate materials: theory meets experiments

Abstract: Herein is presented a theoretical study of the electronic structure and optical properties of six vanadium oxides: Sr2V2O7, Ba2V2O7, Ca2VO4Cl, Sr2VO4Cl, Mg3V2O8 and Zn3V2O8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
6
13
1
Order By: Relevance
“…There it can be seen that the PBE functional considerably underestimate E g , as expected, 40,47 while HSE06 functional provides E g values intermediate between B3LYP and PBE formulations, which only deviate by 10% from the experimental value. The fact that PBE underestimate the band-gap energy by approximately 1 eV (in our and previous studies 13 ) is consistent with recent studies from related vanadates, 47 which showed that the Hubbard U contribution should be included in PBE calculations to properly describe electronic structures of multiple vanadates.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…There it can be seen that the PBE functional considerably underestimate E g , as expected, 40,47 while HSE06 functional provides E g values intermediate between B3LYP and PBE formulations, which only deviate by 10% from the experimental value. The fact that PBE underestimate the band-gap energy by approximately 1 eV (in our and previous studies 13 ) is consistent with recent studies from related vanadates, 47 which showed that the Hubbard U contribution should be included in PBE calculations to properly describe electronic structures of multiple vanadates.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, previous calculations have been carried out using the PBE functional, which is known to underestimate the band gap of vanadates. 47 These reasons and the present calculations indicate that the most correct determination of the band-gap is 3.5 eV. This is supported not only our calculations but also by the white color of Zn 2 V 2 O 7 .…”
Section: Resultssupporting
confidence: 88%
“…In most cases of semiconducting materials, the functionals of LDA-CAPZ and GGA-PBE underestimate the band gap [20,21]. It is reported that the Heyd-Scuseria-Ernzerhof hybrid functional (HSE06) is one of the approaches that is used to calculate a more accurate band gap of semiconducting materials [22][23][24][25]. Therefore, we have tried to explore the band gap using HSE06 along with LDA-CAPZ and GGA-PBE.…”
Section: Electronic Properties Electron Density Difference and Mullik...mentioning
confidence: 99%
“…Energetic calculations for each residue of the drugs binding sites in complex with the receptors PD‐1 and PDL‐1, highlighted in Figure 1, were done by using a gradient corrected DFT (Density Function Theory) framework, [26,27] together with the CPCM (Conductor‐like Polarizable Continuum Model) continuum solvation model [28–30] . A Monkhorst‐Pack 4 × 4 × 4 sampling was employed to evaluate integrals in reciprocal space.…”
Section: Methodsmentioning
confidence: 99%